Emotions in the moral life - Roberts, Robert Campbell, 1942- (New York : Cambridge University Press, 2013)
'Robert C. Roberts first presented his vivid account of emotions as'concern-based construals' in his book Emotions: An Essay in Aid of Moral Psychology (Cambridge University, 2003). In this new book he extends that account to the moral life. He explores the ways in which emotions can be a basis for moral judgments, how they account for the deeper moral identity of actions we perform, how they are constitutive of morally toned personal relationships like friendship, enmity, collegiality, and parenthood, and how pleasant and unpleasant emotions participate in our virtues and vices, and, for better or worse, express our moral character. His rich study will interest a wide range of readers working on virtue ethics, moral psychology, and emotion theory.'--Book Jacket.
Studying virtues -- The roles of emotions: an overview -- Emotions, perception, and moral judgment -- Objections to the perception thesis -- Emotional truth -- Emotions and actions -- Personal relationships -- Emotions and happiness -- Diversity and connection among the virtues.
Includes bibliographical references (pages 212-217) and index.
Keywords: Virtues; Emotions (Philosophy).